2007
DOI: 10.13031/2013.23144
|View full text |Cite
|
Sign up to set email alerts
|

Emissions of Greenhouse Gases from a Typical Chinese Swine Farrowing Barn

Abstract: ABSTRACT. Emissions of greenhouse gases (GHGs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…The CO 2 levels found in these facilities may be up to 0.7% higher than ambient air (Dong et al , 2007), confounding the impact on the seasoned workers who must also contend with airway obstruction developing over time. Shorter common CO 2 exposures such as smoking may result in CO 2 exposures ranging up to 12.5% (Norman, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…The CO 2 levels found in these facilities may be up to 0.7% higher than ambient air (Dong et al , 2007), confounding the impact on the seasoned workers who must also contend with airway obstruction developing over time. Shorter common CO 2 exposures such as smoking may result in CO 2 exposures ranging up to 12.5% (Norman, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…The USEPA Inventory of U.S. Greenhouse Gas Emissions and Sinks (2008) identifies manure management as generating 24 % and 5 % of the methane (CH 4 ) and nitrous oxide (N 2 O) emissions, respectively, from agricultural sources. A review of published literature identified reports of CH 4 and N 2 O emissions from fattening pigs on slatted floors in Denmark (Osada, et al, 1998), from swine farrowing house in China (Dong et al, 2007), swine hoop structures (Singh, et al, 2003), GHG emissions from stored swine manure (Lagu, et al, 2005) and CH 4 and N 2 O emissions data from dairy farms (Singurindy, et al, 2007, Sedorovich, et al, 2007. Very limited published information quantifying GHG emissions from U.S. broiler production systems was found in the literature, however.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, animal manure management accounts for 0.9% of the total national GHG emissions in the U.S. Osada et al (1998) reported CH 4 and N 2 O emissions from fattening pigs on slatted floors in Denmark. GHG emissions M from swine farrowing house in China (Dong et al, 2007), from swine hoop structures (Singh et al, 2003), and from stored swine manure (Laguë et al, 2005) have also been reported. Burns et al (2008) reported GHG, ammonia, and particulate matter emissions from broiler houses in the southeastern U.S.…”
mentioning
confidence: 99%